URGENSI PEMEKARAN KECAMATAN DI KABUPATEN KAPUAS HULU TERHADAP PENINGKATAN KUALITAS PELAYANAN PUBLIK - , Ansela Sarating, SH; , Enny Nurbaningsih, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The research titled âUrgency to the Subdistrict Extension in Kapuas Hulu Regency towards the Increase of Public Serviceâs Qualityâ aims to find out the urgency of the subdistrict extension in Kapuas Hulu Regency and the current condition of public serviceâs quality after the subdistrict extention has been officially enacted. This research combines empiric legal research and normative legal research which is conducted by literature research and field research in Kapuas Hulu Regency, emphasized to residence identification cardâs service in subdistrict. Tools for collecting data in this research are documentary study and interview guidelines. The obtained data then was analyzed with qualitative method to make conclusion. The result shows that urgency to the subdistrict extension in Kapuas Hulu district is the large span of control faced by subdistrict. The large span of control comprises of long distance and time-consuming travels between subdistrictâs capital and villages. The large span of control faced by subdistrict is caused by the extensive area of subdistrict and geographical condition. Those create inefficiency on cost and time for both subdistrict and resident. After subdistrict extension was officially decreed, subdistrict runs public service in functional pattern without applying standardâs service. Having no standard, public service in subdistrict has no benchmark on process, time, cost and quality of product. Subdistrictâs service on residence identification card obviously takes longer time than pre-extension of subdistrict. Each subdistrict puts different expense for service of residence identification card. Looking at the way the public service organized, it can be summarized that subdistrict extention is not yet able to encourage the increase of public serviceâs quality. The Local Government of Kapuas Hulu needs immediately to make regulation for implementation of the Minimum Service Standard on subdistrictâs public service and subdistrictâs integrated administration service, to revise the Regentâs Decree Number 18 of 2000 on Delegation of Some Governmental Authorities from Regent to the Head of Subdistrict as a part of Local Government of Kapuas Hulu therefore delegation of governmental authority is appropriate to Act Number 32 of 2004 on Local Government, and also to synchronize the licensing authority among local governmentâs apparatuses. Besides, the Local Government of Kapuas Hulu is suggested to add government officer and budget for subdistrict in order to increase public serviceâs quality.